Building Resilience to Natural Disasters : An Application to Small Developing States - Marto, Ricardo (IMF Working Papers; Working Paper ;, 2017)
We present a dynamic small open economy model to explore the macroeconomic impact of natural disasters. In addition to permanent damages to public and private capital, the disaster causes temporary losses of productivity, inefficiencies during the reconstruction process, and damages to the sovereign's creditworthiness. We use the model to study the debt sustainability concerns that arise from the need to rebuild public infrastructure over the medium term and analyze the feasibility of ex ante policies, such as building adaptation infrastructure and fiscal buffers, and contrast these policies with the post-disaster support provided by donors. Investing in resilient infrastructure may prove useful, in particular if it is viewed as complementary to standard infrastructure, because it raises the marginal product of private capital, crowding in private investment, while helping withstand the impact of the natural disaster. In an application to Vanuatu, we find that donors should provide an additional 50% of pre-cyclone GDP in grants to be spent over the following 15 years to ensure public debt remains sustainable following Cyclone Pam. Helping the government build resilience on the other hand, reduces the risk of debt distress and at lower cost for donors.